Experimental techno-economic analysis of an autonomous photovoltaic system operating in Chocó (2024)
Despite of scientific efforts to evaluate economically the photovoltaic plants integrating the costs generated by the technical behavior of the system, few studies have demonstrated the behavior of the economic parameters from experimental data obtained from the photovoltaic plants in real-time operation. On the other hand, the cost analysis carried out by various authors breaks down the equation for calculating the Levelized cost of energy in independent terms without considering the marketing options of local markets in remote regions. This article discusses the results of a lead–acid battery system monitored over six years of operation. The system is part of a 20 kWp independent, modular photovoltaic power plant and is divided into two parallel circuits, each consisting of 24 batteries. Technical parameters such as state of charge, Pb-A system voltage, temperature, and charge/discharge currents were monitored, along with power flow before and after the Pb-A system inverter. The incremental charge/discharge efficiency between two parallel circuits, the duration of the charge and discharge cycles, and the Coulombic efficiency were evaluated from the measured data. A statistical analysis of the state of charge was performed to specify the energy delivered from the series of battery banks. This allowed for an evaluation and understanding of the operational performance of the photovoltaic system from a technical and economic point of view. The average minimum and maximum state of charge for bank 1 was 78.9% and 99.96%, respectively, and for bank 2 was 78.15% and 99.83%, respectively, for the monitored period. The efficiency of the incremental cycle varies for Sb1 from 92% to 99% and for Sb2 between 80% and 99%. From the monitoring of these parameters and using actual costs, the Levelized Cost of Electricity was determined for various discount rates.